The trade in domestic workers : causes, mechanisms and consequences of international migration - Heyzer, Noeleen, ed (Kuala Lumpur : Asian and Pacific Development Centre, 1994)
Selected papers from a regional policy dialogue on "Foreign Women Domestic Workers: International Migration, Employment and National Policies, Colombo, Sri Lanka, 10th-14th August 1992
Keywords: Contract workers, Overseas -- Women; Domestics -- Women; Emigration and immigration -- Congresses